Pulmonary Arterial Hypertension in Systemic Lupus Erythematosus: Current Status and Future Direction. (2012) - Dhala, Atiya
Abstract : Pulmonary arterial hypertension (PAH) is commonly associated with connective tissue diseases (CTDs) including systemic sclerosis and systemic lupus erythematosus (SLE). The prevalence of PAH in SLE is estimated to be 0.5% to 17.5%. The pathophysiology of PAH involves multiple mechanisms from vasculitis and in-situ thrombosis to interstitial pulmonary fibrosis which increases pulmonary vascular resistance, potentially leading to right heart failure. Immune and inflammatory mechanisms may play a significant role in the pathogenesis or progression of PAH in patients with CTDs, establishing a role for anti-inflammatory and immunosuppressive therapies. The leading predictors of PAH in SLE are Raynaud phenomenon, anti-U1RNP antibody, and anticardiolipin antibody positivity. The first-line of diagnostic testing for patients with suspected SLE-associated PAH (SLE-aPAH) involves obtaining a Doppler echocardiogram. Once the diagnosis is confirmed by right heart catheterization, SLE-aPAH patients are generally treated with oxygen, anticoagulants, and vasodilators. Although the prognosis and therapeutic responsiveness of these patients have improved with the addition of intensive immunosuppressive therapies, these treatments are still largely unproven. Recent data put the one-year survival rate for SLE-aPAH patients at 94%. Pregnant women are most at risk of dying due to undiagnosed SLE-aPAH, and screening should be considered essential in this population.